The theory of multi-level governance conceptual, empirical, and normative challenges - Piattoni, Simona, 1960- (Oxford : Oxford University Press, 2010)
This title explores the theoretical issues, empirical evidence and normative debates elicited by the concept of multi-level governance (MLG). Three policy areas are investigated in vindicating the usefulness of MLG as a theoretical and empirical concept, with particular reference to the UK and Germany.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Decentralization in government -- European Union countries; Decentralization in government